Do Not Neglect the Body and Action: The Emergence of Embodiment Approaches to Understanding Human Development. Issue 3 (June 2019) - Marmeleira, José; Duarte Santos, Graça
It is becoming clear that to truly understand what it is to be human, focusing scientific efforts on the mind alone is insufficient. We are embodied minds, living and acting in a world full of meaningful things. In this article, we discuss how science has been informed by important research insights into the close relationship between the body, the mind, and the world. These interactions can be translated into embodied perspectives of human development. We provide evidence that perception, cognition, emotion, human relations, and behavior are grounded in our bodies from the beginning of our lives. From this perspective, the body cannot be assumed to be simply an effector for cognition or an instrument for collecting information for the brain. This comprehensive review and debate of embodied-related literature is accompanied by the identification of theoretical challenges and practical applications that will shape research for years to come.